Perinatal derivatives application: Identifying possibilities for clinical use - Gindraux, Florelle; Hofmann, Nicola; Agudo-Barriuso, Marta; Antica, Mariastefania; Couto, Pedro Silva; Dubus, Marie; Forostyak, Serhiy; Girandon, Lenart; Gramignoli, Roberto; Jurga, Marcin; Liarte, Sergio; Navakauskiene, Ruta; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Perinatal derivatives (PnD) are drawing growing interest among the scientific community as an unrestricted source of multipotent stromal cells (MSC), stem cells, cellular soluble mediators, and biological matrices. They are useful for the treatment of diseases that currently have limited or no effective therapeutic options by means of developing regenerative approaches. In this review, to generate a complete view of the state of the art, a comprehensive 10-year compilation of clinical-trial data with the common denominator of PnD usage has been discussed, including commercialized products. A set of criteria was delineated to challenge the10-year compilation of clinical trials data. We focused our attention on several aspects including, but not limited to, treated disorders, minimal or substantial manipulation, route of administration, dosage, and frequency of application. Interestingly, a clear correlation of PnD products was observed within conditions, way of administration or dosage, suggesting there is a consolidated clinical practice approach for the use of PnD in medicine. No regulatory aspects could be read from the database since this information is not mandatory for registration. The database will be publicly available for consultation. In summary, the main aims of this position paper are to show possibilities for clinical application of PnD and propose an approach for clinical trial preparation and registration in a uniform and standardized way. For this purpose, a questionnaire was created compiling different sections that are relevant when starting a new clinical trial using PnD. More importantly, we want to bring the attention of the medical community to the perinatal products as a consolidated and efficient alternative for their use as a new standard of care in the clinical practice.